Eksplorasi Etnomatematika Pada Rumah Adat Kampung Tago’o: Pengenalan dalam Pembelajaran - A, Klarisa Riavinola M; Making, Samuel R. M.; Kerans, Geterudis; Lede, Yulius Keremata (CT. Rajawali media Utama, 2023)
The purpose of this research is to find out the ethnomathematics in the traditional house of Tago'o Village, North Wewewa District and its introduction in learning at SMA Negeri 1 North Wewewa. This research adopted qualitative and exploratory methods with research subjects consisting of traditional leaders, hosts, and traditional house builders in Tago'o Village. The results revealed several findings related to traditional houses in Tago'o Village, such as the trapezium on the front view of the traditional house tower, the triangular shape seen from the side, and the concept of intersecting lines called karaga umma. The structure of the traditional house shows the use of wood that forms horizontal and intersecting lines, with the pillars of the traditional house forming vertical and perpendicular lines. In addition, the study also identified various geometric shapes such as blocks, rectangles, squares, circles, tubes, spheres and acute angles found in various parts of the traditional house, from the inside such as food storage to the outside such as under the house for pets. These findings provide an overview of the use of mathematical concepts related to the design and structure of the traditional houses of Tago'o Village. The implication is that this knowledge can be applied in the context of learning at SMA Negeri 1 Wewewa Utara to enrich students' understanding of mathematics in everyday life based on local wisdom.